2015
DOI: 10.1136/tobaccocontrol-2015-052560
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ and adults’ perceptions of ‘natural’, ‘organic’ and ‘additive-free’ cigarettes, and the required disclaimers

Abstract: Objectives We sought to investigate adolescents’ and adults’ perceptions of an American Spirit advertisement with “natural,” “organic,” and “additive-free” descriptors and related disclaimers. Methods We conducted 9 focus group discussions in the Southern US, with 59 participants ages 13 to 64 (30 male, 29 female), stratified by age, smoking status, and susceptibility to smoking. We conducted thematic content analysis of the transcripts. Results Many participants were skeptical or confused about the “natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 20 publications
3
31
0
Order By: Relevance
“…NAS smokers are 22 times more likely than other smokers to believe that their brand is less harmful than other cigarette brands. Taken in context with prior research,3 4 these results suggest that NAS smokers are concerned about the harms associated with their smoking. Adult NAS smokers may choose the NAS brand because they perceive it as a less harmful cigarette product as a result of NAS branding and/or the descriptors ‘organic’, ‘natural’ and ‘additive-free’ on product packaging and advertising.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…NAS smokers are 22 times more likely than other smokers to believe that their brand is less harmful than other cigarette brands. Taken in context with prior research,3 4 these results suggest that NAS smokers are concerned about the harms associated with their smoking. Adult NAS smokers may choose the NAS brand because they perceive it as a less harmful cigarette product as a result of NAS branding and/or the descriptors ‘organic’, ‘natural’ and ‘additive-free’ on product packaging and advertising.…”
Section: Discussionsupporting
confidence: 77%
“…Market share for NAS grew 554% between 2002 and 2013 among all age groups and, according to the most recently available data, was the fifth most popular cigarette brand among US young adults aged 18–34 years between 2011 and 2014 (following Marlboro, Newport, Camel and Pall Mall) 16 17. This recent increase in market share and popularity with young consumers may be due to the brand's packaging and advertising conveying unsubstantiated reduced harm messages, which have not been corrected by the settlement-required disclaimers 3 4. Indeed, misperceptions of harm associated with ‘natural’ and ‘additive-free’ cigarettes have also been shown to be associated with intention to purchase the brand 5.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have highlighted that no conclusive evidence indicates that the advertised ‘natural’ attributes of NAS make NAS cigarettes any less harmful than traditional cigarettes; thus, as research continues to provide validation of prior non-experimental findings about NAS advertising effects (which our study does), ‘it may be appropriate for regulatory agencies to ban ‘natural’, ‘organic’ and ‘additive-free’ descriptors’ (p520), a regulatory action which such agencies have not yet taken 10. As a result, the findings of this study offer further evidence for regulators considering the ramifications of claims used in the marketing of natural cigarettes.…”
Section: Discussionmentioning
confidence: 57%
“…Content analytic findings pertaining to NAS advertisements have identified several attributes, including textual claims about organic tobacco and sustainable growing practices, as well as images of plants, that could contribute to misperceptions of reduced harm 3. Focus group findings have demonstrated that smokers often believe NAS cigarettes pose lower health risks, doubt the veracity of pack warning labels and cite these misinformed beliefs as a reason for smoking NAS 10. Survey results further indicate that smokers, especially those who use NAS, believe the brand to be less harmful and attend to health considerations more than other smokers 11 12.…”
Section: Introductionmentioning
confidence: 95%
“…Already our results strongly support the US Food and Drug Administration's warning letters to the makers of American Spirit7 and Winston8 cigarettes that claim that the use of the terms ‘additive-free’ and ‘natural’ conveys that these cigarettes are ‘modified risk tobacco products’. That the majority of American Spirit's users believed these cigarettes were less harmful in spite of disclaimers that state ‘No additives does NOT mean a safer cigarette’ confirms the findings of focus groups that suggest that these disclaimers are not sufficient to eliminate harm misconceptions 9. Moreover, our results reinforce the notion that tobacco manufacturers' removal of the terms ‘light,’ ‘mild’ and ‘low-tar’ in 2010 has not eliminated the misconception that these now ‘light-coloured’ cigarettes might be less harmful 10.…”
Section: Discussionmentioning
confidence: 70%